Perioperative complications following spinal fusion in idiopathic scoliosis: A review of 825 cases from the German Spine Registry (DWG-register) – Perioperative complications in idiopathic scoliosis - Juan Manuel Vinas-Rios; Vincent J. Heck; Fatima Azucena Medina-Govea; Mario Alberto Islas-Aguilar; Nikolaus Kernich (Journal of Craniovertebral Junction and Spine)
Background: Overview of the literature: Idiopathic scoliosis (IS) is most commonly developed during adolescence and affects 2%–3% of the population. The overall complication rate for corrective surgeries in adolescent IS patients is described as 6.3%. Perioperative complications include intraoperative blood loss, neurological deficit, and infection, with excessive blood loss being one of the most common. The aim of the study is to evaluate the prevalence of major and minor complications following posterior or anterior fusion for IS. Methods: Retrospective multicenter study of data from the DWG-Register of patients who underwent operative treatment for IS from January 2017 to September 2022. Inclusion criteria: IS, age between 10 and 30 years. Results: In total, 825 IS patients undergoing fusion were identified in the registry; n = 801 (Group 1) did not have operative complications and n = 24 had a complication related to surgical procedure (Group 2); therefore, the complications rate was 2.9%. A 1.3% rate of major complications and 1.6% rate of minor complications were recorded as follows: spinal cord damage n = 2 (8.4%), subfaszial hematoma n = 2 (8.4%), motor dysfunction n = 1 (4.2%), cerebrospinal fluid (CSF)-leakage n = 7 (29.2%), sensory dysfunction n = 6 (25%), bowel/bladder dysfunction n = 1 (4.2%), superficial site infection n = 2 (8.4%), and pulmonary lung atelectasis n = 3 (12.5%). According to the logistic regression model, an odds ratio for pedicel screws versus laminar hooks for hyperkyphosis correction of 3.73 and for Ponte-osteotomy of 11.5 was found. Conclusions: In IS patients treated operatively, the prevalence of nonneurologic postoperative complications following corrective surgery was 1.80% with CSF leak being the leading risk of complication at 0.84.%. These findings should guide surgeons in their intraoperative Dural tear repair particularly osteotomies. Alternate level pedicle-screw placement with laminar hooks leads to higher operation time and more extensive fusion with consequent slightly prevalence in perioperative complications.